Oncological emergencies associated with gastrointestinal tumors - Prenen, Klaas (Ann Gastroenterol, 2015)
Oncological emergencies are defined as acute life-threatening conditions in cancer patients either as a result of the malignancy or as a result of its treatment. In this review, we focus on oncological emergencies associated with gastrointestinal tumors. They can be categorized by their system of origin as hematologic, neurologic or metabolic. Furthermore, we discuss mechanical emergencies such as intestinal obstruction and vena cava superior syndrome as well as acute gastrointestinal bleeding and pulmonary embolism. The patients’ performance status as well as prognosis are essential during decision making for optimal treatment.